A Different Directorate (2017)
UNAM is a Mexican university that has integrated research and the extension of culture. This university has traveled the path of scientific dissemination that today allows it to be in charge of the Directorate, two museums, media and academic publications. Director Elaine Reynoso counts more of these processes.